Managing the Marine and Coastal Environment of Sub-Saharan Africa : Strategic Directions - Hewawasam, Indu (Directions in Development - General, 2002)
The trends toward ecosystem degradation and social change are affecting coastal areas around the world, not least in Sub-Saharan Africa. The crisis affecting this region's coastal and marine areas requires an urgent and resolute response from the global community. This report details the challenges facing coastal and marine environments in Sub-Saharan Africa. It describes the World Bank's strategy for supporting sustainable development in the sector, while stressing an integrated approach to coastal management in Sub-Saharan Africa, which will be strategic in design, with both traditional investments in fisheries, or coastal biodiversity, and creative interventions for making large-scale investments in infrastructure, or water "coastal friendly", to avert impacts, while bringing tangible benefits to coastal populations, and ecosystems